Clinical utility of urinary comprehensive genomic profiling in diagnosing metachronous upper tract urothelial carcinoma: a case report - Yonover, Paul M.; Ward, Ceressa T.; Mazzarella, Brian C.; Phillips, Kevin G.; Jensen, Brad W.; Bicocca, Vincent T.; Duffy, Kathleen; Yonover, Jaden; Cherry, Ava; Levin, Trevor G. (Frontiers in Urology, 2023)
Introduction and aim of study: Metachronous upper tract urothelial carcinoma (UTUC) is a rare yet aggressive malignancy that is often multifocal and invasive at the time of diagnosis. Unfortunately, the rarity of metachronous UTUC results in a paucity of targeted data, as current literature and clinical management of this tumor is largely extrapolated from that of bladder cancer. Urinary comprehensive genomic profiling with the UroAmp assay identifies six general classes of tumor-mutations present in the urine and thus, may aid in detecting UTUC when the limitations of current tools impede definitive diagnosis. We describe the utility of urinary comprehensive genomic profiling in confirming the provider’s suspicion for metachronous UTUC and recommending radical nephroureterectomy. Patient case: A 68-year-old male with a history of recurrent carcinoma in situ (CIS) of the bladder presented to the urology clinic in 2022 for continued surveillance. Abnormal soft tissue thickening surrounding the proximal right ureter, revealed on computerized tomography urography, prompted further evaluation. Selective right upper tract cytology was indeterminate, and urinary comprehensive genomic profiling was ordered to adjudicate. No tumor was visualized on ureteroscopy, however, the cytologic brush biopsy of the renal pelvis and proximal ureter were positive for urothelial carcinoma (UC) and/or CIS. UroAmp testing identified genomic features associated with high-grade UC, risk of invasion, and a high genomic disease burden. Results: The patient underwent a right kidney and ureter nephroureterectomy in September 2022. Surgical pathology confirmed non-invasive multifocal urothelial CIS. A postoperative urinary comprehensive genomic profiling in February and May of 2023 detected no evidence of residual disease, consistent with complete resection of the tumor. The provider will continue intensive urinary comprehensive genomic profiling monitoring coupled with conventional surveillance. Conclusion: Urinary measurement of mutated urothelial carcinoma genes correlate with disease burden, pathologic grade, and invasion risk and provided clinical utility when reliance on visual confirmation and cytology were not definitive or feasible.